Implementasi Kebijakan Penyelenggaraan Kesejahteraan Sosial terhadap Penanganan Gelandangan dan Pengemis di Kota Sukabumi - Rifaldi Irfan, Muhammad; Mulyadi, Andi; Hegia Sampurna, Rizki (Jurnal Ilmiah Administrasi Publik, 2024)
This study investigates the implementation of the Social Welfare Implementation Policy on the handling of vagrants and beggars in Sukabumi City by referring to the six perspectives of successful policy implementation according to Van Metter and Van Horn which include Policy Standards and Objectives, Utilization of Resources, Communication between Organizations that play a role, Characteristics of Implementing Agents, Attitudes of Implementers, Economic, Social and Political Environment in creating success. The method used was a qualitative study by conducting interviews with 3 informants from the Sukabumi City Social Service and then the results of the interviews were written descriptively in the form of words in accordance with the problems studied and the situation that was happening. The results showed that the implementation of this policy was considered quite good. Policy standards and objectives were followed in accordance with the Minimum Service Standards (MSS), while resource utilization, especially funding sources, still required more attention. Inter-organizational communication, characteristics of the implementing agents, and attitudes of the implementers are considered positive, with maximum support from the economic and social environment of the community. Nonetheless, communication complexity and some constraints, such as multiple commitments and program complexity, became barriers to implementation. The conclusion states that a supportive external environment can contribute greatly to successful implementation.